The story of the world/ Volume 2/ From the Fall of Rome to the Rise of the Renaissance - Bauer, S. Wise.; Weiss, Jim (Charles City, Va. : Open Texture/Peace Hill Press, 2007)
Presents a history of the ancient world, from 6000 B.C. to 400 A.D.
Socials
Global
Middle Ages
Read by Barbara Alan Johnson.
Compact discs.
Set includes: 6 compact discs.
Keywords: Middle Ages -- Juvenile sound recordings; World history -- Juvenile sound recordings; History, Ancient -- Juvenile sound recordings; Civilization, Medieval -- History -- Juvenile sound recordings; Europe -- History -- Juvenile sound recordings; Africa -- History -- Juvenile sound recordings; America -- History -- Juvenile sound recordings; East Asia -- History -- Juvenile sound recordings